Synthesis, characterization, and ionic conductivity of electrospun organic-inorganic hybrid gel electrolytes - KAYAMAN APOHAN, NİLHAN (WILEY, 2020)
In this work, we described the synthesis of organic-inorganic hybrid gel electrolytes combining electrospinning, sol-gel, and ultraviolet (UV) curing techniques in order to investigate their ionic conductivity properties. First, 3-glycidyloxypropyl trimethoxysilane modified polyamic acid and alkoxysilane functional poly(dimethyl siloxane) were electrospun together. Then, the following thermal imidization, the obtained fiber was cured in the UV curable gel formulation. To improve the interaction between fiber and gel matrix, 3-(trimethoxysilyl)propyl methacrylate was partly hydrolyzed and then used as a bifunctional crosslinker. Finally, the membrane was soaked into 0.5 M LiFP6 salt solution to obtain organic-inorganic hybrid gel electrolytes. The chemical structure, ionic conductivity, and range of electrochemical stability window of the photocured nanocomposite electrolytes were investigated by using FTIR, thermogravimetric analysis, differential scanning calorimetry, electrochemical impedance spectroscopy, linear sweep voltammetry, and SEM analysis. The acquired results from experiments indicate that a convenient nanocomposite electrolyte for lithium-ion batteries with high electrolyte (Li salt) uptake, adequate conductivity (1.02 x 10(-3) S cm(-1)) at ambient temperature and electrochemically stable between 1 and 6 V had been prepared. POLYM. ENG. SCI., 2019. (c) 2019 Society of Plastics Engineers
Keywords: POLYMER ELECTROLYTES; NONWOVEN SEPARATORS; FACILE FABRICATION; THERMAL-PROPERTIES; LITHIUM; MEMBRANE; PERFORMANCES; NANOFIBERS; BEHAVIOR; BATTERY